Torsion modulus to hollow glass microsphere additives in unsaturated polyester resin: Dynamic and deformation energy methods - Pintão, Carlos Alberto Fonzar [UNESP] (2024)
This paper presents two methods for deformation energy or dynamic for measuring and calculating the torsion modulus, G, for composites with hollow glass microsphere (HGM) additives in unsaturated polyester resin. First, we constructed a measurement system with a torsion pendulum, a force sensor (FS), and a rotational movement sensor (RMS). Then, we deduced a relationship between force (F) and torsion angle (θ) to obtain G by deformation energy. Second, using the relaxation curve, θ in function time (t), we deduce an equation that could return the value of G for dynamic. Both techniques are non-destructive and independent of knowing the value of Poisson’s ratio. We used samples of approximately 5.00 mm diameters, and the influence percentage of HGM additives differed from that of 100%Wt resin. They obtained G values by opting for these composite materials’ different methods, showing a maximum deviation of 5.44%.